Evaluation of the impact of the “Classroom without Violence” Program for adolescents - Flores Perez, Virginia; Camacho Ruiz, Esteban Jaime; Alvarez Rayón, Georgina Leticia (IE Revista de Investigación Educativa de la REDIECH, 2024)
Through the design and implementation of intervention programs, an attempt has been made to prevent, address and/or eliminate school violence which is present in basic education institutions, especially in elementary and middle schools, and even more so since the magnitude of this problem has been demonstrated in various international and national surveys, which is why it has been considered a priority issue in education and health. The objective was to evaluate the impact of a program against school violence on teenagers. The sample included 118 adolescents (61 females and 57 males) aged 11 to 16 years (M = 13.04, SD = 1.03), from a public high school in the municipality of Chimalhuacán, State of Mexico. The Self-Esteem Scale for adolescents and the School Violence Evaluation Questionnaire for Infants and Primary School were used and answered before and after the intervention. The program consisted of six 50-minute weekly sessions. Sessions were given by health educators. The repeated anova measurements test showed statistically significant differences for the variables self-esteem and school violence for the intervention group from pretest to post-test...